2019
DOI: 10.31883/pjfns/112643
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Aromatic Vinegar in Reducing Psychrotrophic Bacteria and Biogenic Amines in Salmon Fillets (Salmo salar) Stored in Modified Atmosphere Packaging

Abstract: Salmon esh spoilage can be greatly reduced through the use of preservation methods, using natural products combined with low temperature and packaging. Microbiological and physicochemical characteristics of fresh salmon llets (Salmo salar), sprayed with an aromatic vinegar and stored in modi ed atmosphere packaging, were investigated. Fillets were kept at 4°C and sampled after 2 h and 3, 7 and 10 days. An untreated control group was used as well. Fish samples were analysed for microbiological (total viable cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It was reported that aromatic vinegar beneficially exerted a positive effect on the inhibition of microbial growth during storage of Salmon fillets, especially on psychrotrophic bacteria and Pseudomonas spp (Toro et al., 2019). In present study, the higher inhibitory effect of salting with Chinese liquor on microbial growth is mainly related to the higher alcohol concentration of 65% (v/v), and other compounds including organic acids and polyphenols in Chinese liquor may also play a role to some extent due to the limited concentration.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that aromatic vinegar beneficially exerted a positive effect on the inhibition of microbial growth during storage of Salmon fillets, especially on psychrotrophic bacteria and Pseudomonas spp (Toro et al., 2019). In present study, the higher inhibitory effect of salting with Chinese liquor on microbial growth is mainly related to the higher alcohol concentration of 65% (v/v), and other compounds including organic acids and polyphenols in Chinese liquor may also play a role to some extent due to the limited concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The uses of citric, ascorbic, acetic, vinegar, capric acid, sodium acetate, and lactic acid for preserving FFP are summarized in Table 1. Vinegar as aromatic vinegar was evaluated in enhancing the microbial quality of salmon fillets stored under modified atmosphere packaging at 4° C for 10 days (Di Toro et al., 2019). Vinegar reduced the Enterobacteriaceae and psychrotrophic counts during storage while having no significant effect on the total viable count.…”
Section: Application Of Antimicrobials From Natural Sources For Ffp P...mentioning
confidence: 99%